The Distributed Impact of Price-Level Variation on Floating Exchange Rates - Hodgson, John S.; Phelps, Patricia (The Review of Economics and Statistics, 1975)
T'HIS paper presents evidence on the shortrun characteristics of purchasing-power parity (PPP) theory when account is taken of the fact that the relationship between currency purchasing powers and exchange rates is distributed over time. Distributed-lag variants of PPP theory are tested using price-level data and exchange rates between fourteen foreign currencies and the United States dollar during the period of floating exchange rates in the early 1920's. The findings suggest that in most cases the major impact of price-level movements occurred within a few months following the initial disturbance, and that the distributed effects were largely dissipated within a year's time.